THE EFFICANCY OF DIODE LASER ND:YAG IN ROOT CANALS AND PERIAPICAL LESIONS - Agron Bytyqi; Xhevdet Aliu; Arben Mucaj; Neada Hysenaj (European Scientific Journal, ESJ, 2014)
In our study we tested the efficacy of disinfection with diode laser Nd : YAG root canals of single-rooted teeth and lesion models of different sizes (6, 10 and 14 mm), in which we put the teeth and made an in vitro model. Teeth and models we re-infected with E. faecalisor and S. mitis, as one of the most common microbes for re-infection, till the growth of the biofilm. The growth of the biofilm was confirmed microbiologically on agar plates. Viability of microorganisms in the samples after laser treatment and compared to samples without treatment, were analyzed with a fluorescence method by flow Cytometry. Therapy with diode laser Nd : YAG showed a significant increase in the percentage of dead cells compared to the control group. At the same time we have found a significant difference between the different dimensions of periapical lesions. The smallest dimension lesions of 6 mm showed the highest number of dead cells. When compared E. faecalis and S. mitis we have not found any difference between the sizes of lesions, or between the duration of irradiation. These results indicate that the laser diode does not have the best toxic effects of heat, which is produced by the laser radiation, so the diode laser Nd : YAG radiation alone could not destroy all bacteria, so re-infection is still possible. However, we think that application of laser in combination with the standard methods of irrigation and instrumentation or the application of dyes for photodynamic therapy, we could obtain greater efficacy of disinfection.